Surface treatment of polystyrene films with inductively coupled plasma system - R. Nakhowong (2018)
The surface of polystyrene (PS) thin films in argon plasma was modified to study the hydrophilicity properties. An inductively coupled plasma (ICP) system was used to generate the argon plasma. In the experiment, the effect of RF power levels, gas flow rate and treatment time was investigated. The surface morphology of PS films was examined by the atomic force microscopy (AFM), also the contact angle goniometry was used for measuring the wettability of PS films before and after plasma treatment. After the plasma treatment, AFM images of PS revealed the increasing of the surface roughness as increasing the power levels and treatment times. Moreover, after treated with argon plasma, the contact angles of polystyrene films also decrease where the power levels and treatment times were increased. It is clear that the effects of power levels and treatment time improve the wettability of PS films. It can also be observed that by placing the sample in air after plasma treatment, the contact angle gradually increases probably due to moisture absorption in the PS films. © 2008 Trans Tech Publications, Switzerland.